Courage is contagious : and other reasons to be grateful for Michelle Obama - Haramis, Nicholas (Lenny, 2017)
Here are some of the many facets of Michelle Obama as she continues to inspire us, a stirring reminder that the best of America once lived in the White House, embodied in one authentic, inclusive, and courageous woman.----Miranda July, author of--